Efektivitas Penyidikan di Era Digital: Studi Kasus Inovasi Teknologi di Kepolisian Resor Rokan Hilir - Sihombing, Rikky Pranata; Kusno, Kusno; Siregar, Ahmad Ansyari (CV. Social Politic Genius (SIGn), 2024)
This study aims to analyze the extent to which implemented technological innovations enhance investigative effectiveness and identify the supporting factors and obstacles to technology adoption at the Rokan Hilir Police Resort. To achieve these objectives, this study employs a mixed-methods approach combining field research and normative legal analysis, where the collected data is analyzed qualitatively to describe the issues and address the research objectives. The findings indicate that technology implementation at the Rokan Hilir Police Resort positively impacts investigative effectiveness, particularly in terms of speed and efficiency, accountability and transparency, and inter-unit coordination. Furthermore, technology plays a crucial role in evidence management, improving data accuracy, and handling complex cases, as demonstrated in the digital theft case study. The application of investigative technology at the Rokan Hilir Police Resort aligns with the relevant legal framework in Indonesia. However, technology implementation still faces challenges such as budget limitations, lack of technological skills, and resistance to change. Nevertheless, this study finds that technological innovation at the Rokan Hilir Police Resort has contributed to increasing public trust in the police institution, suggesting that the modernization of investigations through technology adoption is a strategic step that needs continuous support and optimization.